Risk Attitudes and Profits among Small Enterprises in Nigeria - Judith Lammers; Daan Willebrands; Joop Hartog (Tinbergen Institute, 2010)
This paper analyses the effect of risk attitudes of firm owners on profits among micro and small enterprises (MSEs) in Lagos, Nigeria. Higher risk perceptions are shown to have a significant positive effect on profits, whereas risk propensity has a negative or no effect. Education, age, being male, and firm size are all positively related to profit, while young firms earn lower profits. Overall, the results suggest that being aware and dealing cautiously with risk leads to higher profitability.
Keywords: D12; L25; L26; 330; entrepreneurship; risk perception; risk behavior; profit; MSEs; Entrepreneurship-Ansatz; Risikomanagement; Unternehmenserfolg; KMU; Lagos; Nigeria